Destructive and Reparative Processes in Rat’s Skin After Burn in Presence of Stem and Progenitor Cell Bioregulators - Cherkashina, Daria V.; Revenko, Olena B.; Rogulska, Olena Yu.; Petrenko, Oleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 024–028